RATIO OF THE MAIN DIMENSIONS AND STATIC STABILITY TRADITIONAL PURSE SEINER IN PINRANG - Muh. Arkam Azis; Budhi Hascaryo Iskandar; Yopi Novita (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The fishing vessel is the main vehicle of the fishermen to go to fishing ground and hauling purse seine especially fishing gear. Pinrang Regency ships traditionally built without calculation of naval architecture. Where the purse seine fishing gear in Pinrang Regency has length 330 m nets with a depth of 36 m. The purpose of this research was to examine the main dimension ratio in particular design and static stability of the vessel purse seine in Pinrang Regency. Method of using a case study on two types of vessels have different relative and analyzed by numerical simulation, calculate the ratio of the main dimensions and static stability. The results of this research are the vessels in Pinrang kasko model has the shape of a round bottom and slim body as well as the ratio of the dimensions of the vessels only L/D purse seine LOA 24 m more than the standard reference of vessels (encircling) in Indonesia and on the value of the static stability by the IMO, with a purse seine vessel Pinrang already has a good stability. However, in both types of vessel purse seine size 20 m that has better stability. Keywords: design, fishing vessel, purse seine, stability